ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENDUKUNG PENGENDALIAN INTERNAL PEMBERIAN KREDIT PADA PT. BANK TABUNGAN NEGARA (BTN) DI KOTA BANDA ACEH - Purwono, Resti Febi; Fachruddin, Rudy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
This study aims to analyze the future of accounting information systems in supporting the internal control of lending carried out by PT Bank Tabungan Negara Banda Aceh Branch. The type of investigation in this study is qualitative research, while the research method that used in this study is descriptive. The data collection technique in this study is through interviews and documentation.The credit accounting information system which implemented by PT Bank Tabungan Negara (BTN) Banda Aceh is adequate and the credit accounting information system has played a role in supporting internal control, and internal control at Bank BTN Banda Aceh has been running effectively